Enrofloxacin and ciprofloxacin residues in broiler chicken post administration of enrofloxacin - Raphaella Widiastuti (Indonesian Center for Animal Research and Development (ICARD), 2008)
The presence of drug residue in animal product may threat human health such as increasing resistance to Camplyobacter infection treatment due to the use of enrofloxacin. The objectives of this research was to study the concentration of enrofloxacin (EFX) and ciprofloxacin (CFX) residues distributed in breast, thigh and liver and to determine the elimination rate of such residues in chicken which recieved enrofloxacin orally at 50 mg/kg bw daily for 9 days consecutively started at 23rd day to 31st day of age. Samples of breast muscle, thigh and liver were collected from chicken at ½ to 288 h after the drug administration. The concentration of EFX and CFX in samples were analyzed by high pressure liquid chromatography (HPLC). The results showed that the highest residues concentration of EFX and CFX at ½ hr post administration of EFX was: in liver (117.47 ng/g), breast (95.16 ng/gr) and thigh (71.40 ng/g), whereas the order of elimination rate was: thigh (120 hr), liver (168 hr) and breast (240 hr). The results also showed that concentration of CFX was higher than that of EFX. Key Words: Enrofloxacin, Ciprofloxacin, Residues, Broiler Chicken